The terrain of thingworlds: Central objects and asymmetry in material culture systems. (June 2021) - Lucas, Gavin; Robb, John
Material culture forms a relational system of distributed reality – a thingworld. But how do we get beyond simply saying that all material culture is meaningful and entangled to understanding the internal structure of such systems? Is it a flat terrain among co-equal things? Or are some objects more important than others, as we might intuitively suppose? And if so, why? This article presents an initial discussion of the problem. Using vignettes from two thingworlds – one from early modern Iceland, one from Neolithic Europe– the authors discuss what were the central material things in each, and for what reasons. This suggests that objects may be systemically central in different ways, for instance things which connect and mediate relationships of different kinds, things which are non-substitutable, and things which span multiple roles and contexts.